Black hair: A crown of glory and versatility. - Jeter, Tonya; Crittendon, Denise (Crisis (00111422), 1994)
Focuses on the hairstyles of African-Americans. Spendings on cosmetics and personal grooming services; New York City, New York hair care specialist Ademola Mandella's `Fade-Away' haircut; Exploration on the heights of hair; Comments of hair stylist Allen Biggers on the flexibility of Afro-American hair; Influence of Europeans on Afro-Americans' perception on the standard of beauty.